2000
DOI: 10.1046/j.1365-2699.2000.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Faunal relationships and zoogeographical affinities of mammals in north‐west Africa

Abstract: The nonmarine mammal fauna of the Maghreb region of north‐west Africa is related to that from three potential source areas: the northern Palaearctic (Europe and south‐west Asia; here referred to as the European fauna), subsaharan Africa (the African fauna) and the arid Palaearctic (Sahara Desert: the desert fauna). On the basis of geographical distribution patterns, this fauna divisible into two groups: the bats, whose affinities are most closely related to southern Europe and south‐west Asia, and nonflying sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 25 publications
2
42
0
1
Order By: Relevance
“…Although only a few kilometers wide (14 km), the Straits of Gibraltar seem to have acted as an important barrier preventing faunal contacts ever since their reopening at the start of the Pliocene about 5.3 million years ago (Dobson and Wright, 2000). Nevertheless, a All values are significant (Po0.05) except for the one depicted in bold type.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although only a few kilometers wide (14 km), the Straits of Gibraltar seem to have acted as an important barrier preventing faunal contacts ever since their reopening at the start of the Pliocene about 5.3 million years ago (Dobson and Wright, 2000). Nevertheless, a All values are significant (Po0.05) except for the one depicted in bold type.…”
Section: Discussionmentioning
confidence: 96%
“…The degree of permeability of the Straits of Gibraltar to bats may be the result of a complex equation in which life history traits are also important. A recent comparative approach including all bat species present on both Iberian and African sides of the Mediterranean has shown the absence of a clear pattern regarding the role of the Straits of Gibraltar on bat communities (García-Mudarra et al, 2009), and caution should be taken when drawing general conclusions (Dobson and Wright, 2000).…”
Section: Table 3 Migration Rate (M) Between Regionsmentioning
confidence: 99%
“…This result suggests that, like insular individuals, those in Morocco originated from the eastern part of Europe. Different routes have been proposed to explain colonization of North Africa (Dobson and Wright, 2000). The absence of genetic similarity between Iberian and Moroccan samples strongly suggests that North African weasels do not come from western Europe (route 1 in Dobson and Wright, 2000).…”
Section: Colonization Of North Africamentioning
confidence: 99%
“…Different routes have been proposed to explain colonization of North Africa (Dobson and Wright, 2000). The absence of genetic similarity between Iberian and Moroccan samples strongly suggests that North African weasels do not come from western Europe (route 1 in Dobson and Wright, 2000). Colonization through this route is, however, advocated for other mammals, including the woodmouse (Apdodemus sylvaticus), which colonized Morocco from the Iberian peninsula (Michaux et al, 2003).…”
Section: Colonization Of North Africamentioning
confidence: 99%
“…The consequences of co-differentiation for the host and parasite histories have already been discussed elsewhere (Nieberding et al, 2004), except for North Africa. In North Africa, paleontological data attest the presence of the wood mouse since 10,000 years only (Dobson, 1998;Dobson and Wright, 2000). Libois et al (2001) and Michaux et al (2003) showed that North African A. sylvaticus reached North Africa via the Strait of Gibraltar as a result of anthropogenic introductions during the Holocene.…”
Section: Regional Co-differentiation Between Heligmosomoides and A Smentioning
confidence: 99%